Brazilian Portuguese Language in the United States: Teaching Portuguese as a Foreign Language in Response to Students’ Language Background - Maria Benicio Valadares , Simoni (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
This paper presents strategies for teaching and learning Portuguese as a third language (L3) in the United States, particularly strategies employed in a Portuguese language course for beginners at the University of New Mexico (UNM) in Albuquerque, NM. The research, based on experience in the classroom, used a collaborative approach that led to an improvement in the process of teaching and learning of a foreign language in elementary courses. The redesign of the course was discussed in relation to the revision of the description and learning outcomes of the course, showing the importance of considering the linguistic profile (i.e., language background) of learners in a foreign language classroom. This research represents a case study in a higher education context for L3 learners whose native or L2 language is Spanish or English.